Unilateral Lichen Aureus in a Child - Case Report - Freitas de Oliveira Góes, Heliana; de Castro Mendes, Marília Troyano; Falci Loures, Aline; Lobato Quattrino, Ada; dos Santos Lima, Caren; Pantaleão, Luciana (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Lichen aureus is a subtype of a chronic benign pigmented purpuric dermatosis of unknown etiology. It shows predilection for lower limbs and generally affects young adults and, less often, children. We report a case of lichen aureus with a unilateral presentation in a child.